A study on the use of oil palm shell in lightweight concrete - Md. Abdul Mannan (2001)
An investigation into the potential use of waste oil palm shells (OPS) as coarse aggregate in concrete construction has been carried out. A suitable mix design of OPS concrete has been established. The long-term performance of OPS and control concretes with fly ash as partial cement replacement has been studied. All samples are tested under four curing conditions. The engineering properties of hardened concrete samples are determined using compressive strength tests, flexural strength tests, splitting tensile tests, modulus of elasticity tests and drying shrinkage tests. A nondestructive test, i. e. ultrasonic pulse velocity test also is performed. To ascertain concrete durability, the initial surface absorption tests, strength tests at high temperatures and performance test in MgS04 solution have been conducted. The most satisfactory performance in engineering properties for both types of concrete are observed in full water curing condition. Fly ash as partial cement replacement in OPS concrete is found to decrease the strengths compared with OPS concrete without fly ash. This investigation has concluded that there is a strong possibility for the utilisation of OPS as coarse aggregate in lightweight concrete construction. It can satisfy concerns for technical feasibility along with environmental and economic considerations. In future, the prospect for resource recovery o{ this waste material can be explored further. OPS, commonly regarded as an agricultural waste, could be accepted as a natural resource since OPS concrete has been proven to possess engineermg characteristics comparable to conventional lightweight aggregate.